Using Event Notifications, Solid and Orchestration for Decentralizing and Decoupling Scholarly Communication - Patrick Hochstenbach, Ruben Verborgh and Herbert Van de Sompel (Code4Lib Journal)
The paper presents the case for a decentralized and decoupled architecture for scholarly communication. An introduction to the Event Notifications protocol will be provided as being applied in projects such as the international COAR Notify Initiative and the NDE-Usable program by memory institutions in The Netherlands. This paper provides an implementation of Event Notifications using a Solid server. The processing of notifications can be automated using an orchestration service called Koreografeye. Koreografeye will be applied to a citation extraction and relay experiment to show all these tools fit together.